KADAR PROTEIN, TOTAL MIKROBA, DAN SIFAT FISIK KECAMBAH KEDELAI BERDASARKAN JENIS KEMASAN PADA PENYIMPANAN DINGIN - Solikah .; Siti Aminah; Agus Suyanto (Jurnal Pangan dan Gizi, 2022)
Soybean sprouts have nutritional components and functional characteristics that are better than soybeans. Soybean sprouts are easily damaged, so efforts are needed to maintain shelf life through packaging and storage. This study aimed to determine the effect of packaging type on cold storage on protein content, total microbes, and physical properties (color and weight loss) of soybean sprouts. The study used a completely randomized design with 5 treatments and 5 replications, namely: open container packaging (A), 0.02 mm thickness HDPE plastic (B), 200 ml closed plastic bowl (C), banana leaves (D), and HVS paper. (E). Storage at a temperature of ± 10oC for 3 days. The results showed that the cold storage of soybean sprouts based on the type of packaging did not affect the protein content, but affected the total microbial and physical properties (color and weight loss). In determination of the best treatment using the Composite Performance Index (CPI) method, the best results were obtained in treatment B with a protein content value of 12.13%, a total microbe of 1.4x106cfu/g, a color with a value of L* 96.34, and a weight loss of 0.05. %.